The Effect of Leverage on Financial Distress: The Moderating Roles of Executive International Experience and CEO Gender in Indonesian State-Owned Non-Financial Enterprises - Nevia Dian Sasmita; Akhmad Samsul Ulum (Universitas Pekalongan, 2026)
The increasing incidence of financial distress among state-owned enterprises (SOEs) has become a major concern, particularly in emerging economies where firms are required to balance financial performance with public service obligations. This study explores the effect of leverage on financial distress and examines whether executive international experience and CEO gender moderate this relationship. The study adopts a quantitative explanatory approach using panel data derived from the annual reports of Indonesian non-financial SOEs during the 2019–2023 period. The research sample was determined through purposive sampling according to predefined selection criteria. Financial distress was assessed using the Altman Z-Score, while leverage was measured by the debt-to-asset ratio. Executive international experience and CEO gender were treated as moderating variables. The proposed relationships were analyzed using Moderated Regression Analysis (MRA). The findings demonstrate that higher leverage significantly increases the probability of financial distress, indicating that excessive debt financing reduces corporate financial resilience. Furthermore, executive international experience significantly mitigates the negative impact of leverage by enhancing strategic judgment, strengthening financial risk management, and improving the quality of corporate decision-making. However, CEO gender does not exert a significant moderating effect, suggesting that governance quality, managerial competence, and organizational resources play a more decisive role in determining financial stability than the gender of the chief executive officer. This study enriches the literature on financial distress by highlighting the importance of executive capabilities in influencing the effectiveness of capital structure decisions within Indonesian SOEs. The findings also provide practical guidance for government shareholders and corporate boards in formulating executive appointment policies and governance practices that support sustainable organizational performance.